Prevalence and predictors of perceived COVID-19 stigma within a population-based sample of adults with COVID-19 - Soomin Ryu; Samhita Chaubal; Paula Guro; Elizabeth J. King; Robert Orellana; Nancy L. Fleischer; Jana L. Hirschtick (BMC, 2023)
Abstract Background Growing evidence suggests that individuals with COVID-19 face stigmatization, which is associated with poor health outcomes and behaviors. However, very few population-based studies have examined risk factors for experiencing COVID-19 stigma. This study examined prevalence and predictors of perceived COVID-19 stigma using a population-based probability sample of adults with COVID-19. Methods We included adults with polymerase chain reaction-confirmed SARS-CoV-2 in Michigan between January 1, 2020 and July 31, 2021. Perceived COVID-19 stigma was considered present if a respondent answered affirmatively to any of the following items due to people thinking they might have COVID-19: "you were treated badly," "people acted as if they were scared of you," and "you were threatened or harassed." We conducted modified Poisson regression with robust standard errors to estimate associations between perceived COVID-19 stigma and potential predictors, including sex, age, race and ethnicity, household income, education, employment, smoking status, body mass index, preexisting diagnosed physical or mental comorbidities, and COVID-19 illness severity. Results Perceived COVID-19 stigma was commonly reported among our respondents (38.8%, n = 2,759). Compared to those over 65 years, respondents who were 18 − 34 (adjusted prevalence ratio (aPR): 1.41, 95% confidence intervals (CI): 1.12 − 1.77) and 35 − 44 years old (aPR: 1.66, 95% CI: 1.31 − 2.09) reported higher perceived stigma. Female respondents had 1.23 times higher prevalence of perceived COVID-19 stigma (95% CI: 1.10 − 1.37) than male respondents and non-Hispanic Black respondents had 1.22 times higher prevalence of perceived COVID-19 stigma (95% CI: 1.04 − 1.44) than non-Hispanic White respondents. Moreover, respondents with pre-existing diagnosed psychological or psychiatric comorbidities were more likely to report perceived COVID-19 stigma (aPR: 1.29, 95% CI: 1.13 − 1.48) compared to those without diagnosed comorbidities. Respondents with very severe COVID-19 symptoms were also more likely to report perceived COVID-19 stigma (aPR: 1.47, 95% CI: 1.23 − 1.75) than those with asymptomatic or mild symptoms. Conclusions We found that populations who are marginalized in United States, such as females, non-Hispanic Black adults, or individuals with chronic conditions, are more likely to report perceived COVID-19 stigma. Continuing to monitor COVID-19 stigma, especially in vulnerable populations, may provide useful insights for anti-stigma campaigns and future pandemics.